The Effect of Professional Competence, Work Motivation, and Workload,on Nurses Performance in The Patient Ward Sebening Kasih Hospital - Fachrul Rizal; Grace Rumengan; Enrico Adhitya Rinaldi (CV. Inara, 2026)
The research problem arises from indications that some nurses experience difficulties in performing their nursing duties optimally, which can impact the quality of patient care. Unequal distribution of professional competence, low motivation due to a lack of recognition and career development opportunities, and a high workload resulting from an imbalance in the nurse-to-patient ratio are suspected to be the main causes of this decline in performance. The purpose of this study was to analyze the influence of professional competence, work motivation, and workload on nurse performance in the inpatient ward of Sebening Kasih Hospital, Pati. Central Java, Indonesia. This study, a descriptive quantitative study, recruited 42 respondents: nurses working in the inpatient ward of Sebening Kasih Hospital, Pati, who had worked in the ward for at least six months, were permanent or active contract nurses, and were willing to participate. The data collected consisted of primary data collected using a questionnaire. The results concluded that professional competence and work motivation had a positive and significant effect on nurse performance in the inpatient ward of Sebening Kasih Hospital, Pati. Central Java, Indonesia. Workload negatively affected nurse performance. The higher the workload, the lower their performance.